A Conceptual Study of Kandara Sharir from Ayurvedic Samhita - Mayuri U. Thakur; Pravin D. Balutkar (AYUSHDHARA, 2023)
Rachana sharir is an important subject in Ayurveda. To cure any disease basic knowledge of anatomical concept must be required. In Ayurveda many concepts like Kurcha, Jala, Snayu, Kandra were described under Paribhasha (Terminologies) Sharir. Kandara is one of the unique concept of Ayurveda which was very well explained by Aacharya Sushrata in Sharirsthana. These are 16 in number. Rounded type of Snayu is also known as Kandara. Prasaranam and Aakunchanm is function of Kandara. Kandara is also known as Updhatu of Rakta. In modern Science they can be correlated with tendon. According to Sushruta Nidansthana Vishwachi, Grudhrasi diseases were related with Kandara. Many other reference books like Bhavprakash, Sharangdhar, Ashtanag Sangraha also explained Kandara sharir.